Brain regions concerned with perceptual skills in tennis: An fMRI study - Wright, M. J.; Jackson, R. C. (International Journal of Psychophysiology, 2007)
Sporting performance makes special demands on perceptual skills, but the neural mechanisms underlying such performance are little understood. We address this issue, making use of fMRI to identify the brain areas activated in viewing and responding to video sequences of tennis players, filmed from the opponent's perspective. In a block-design, fMRI study, 9 novice tennis players watched video clips of tennis play. The main stimulus conditions were (1) serve sequences, (2) non-serve behaviour (ball bouncing) and (3) static control sequences. A button response was required indicating the direction of serve (left or right for serve sequences, middle button for non-serve and static sequences). By comparing responses to the three stimulus conditions, it was possible to identify two groups of brain regions responsive to different components of the task. Areas MT/MST and STS in the posterior part of the temporal lobe responded either to serve and to non-serve stimuli, relative to static controls. Serve sequences produced additional regions of activation in the parietal lobe (bilateral IPL, right SPL) and in the right frontal cortex (IFGd, IFGv), and these areas were not activated by non-serve sequences. These regions of the parietal and frontal cortex have been implicated in a "mirror neuron" network in the human brain. It is concluded that the task of judgement of serve direction produces two different patterns of response: activations in the MT/MST and STS concerned with primarily with the analysis of motion and body actions, and activations in the parietal and frontal cortex associated specifically with the task of identification of direction of serve.